Influence of training stress on psychological well-being in female college athletes: chain mediating roles of general self-efficacy and psychological resilience - Wang, Z.; Song, P.; Ren, J.; Zhang, J. (Frontiers in Psychology, 2026)
Objective: This study examined female college athletes to explore the association between training stress and psychological well-being. It further investigated whether general self-efficacy and psychological resilience mediate this association.